2018
DOI: 10.15625/2525-2518/56/3b/12739
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation of Mercaptan Using Polycaprolactone as Shell Material Toward Self-Healing Coating Applications

Abstract: Polymer materials incorporating microencapsulated self-healing agents have a wide range of application from paint coating, anti-corrosion coatings to automotive and construction materials. In this research, microcapsules containing reactive mercaptan compound for use in self healing polymers were successfully fabricated via the oil-in-water emulsion method. We employed for the first time the UV-initiated thiol-ene reaction between an alkene-functionalized polycaprolactone and a tetrathiol compound to form the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In-situ polymerization Dual capsules: (1) Diglycidyl tetrahydro-ophthalate (2) PETMP [24] 50 µm a 100 µm a -Self-healing composite Dual capsules: (1)Epoxy prepolymer (EC 157) (2) PETMP [25] 10-35 µm 5-45 µm -Self-healing composite Solvent Evaporation PETMP [26] 160 µm a -Self-healing composite epoxy resin (diglycidyl ether of bisphenol A) [32] 575 µm a -Self-healing composite Dual capsules: (33) (1) epoxy resin (DGEBPA) (2) PETMP [33] 364 µm a 334 µm a 3-6 µm Self-healing composite Budesonide and Epigallocatechin gallate (EGCG) [27] 165 nm to 1.2 µm -Coating of drug Paclitaxel [28] 600 nm-6 µm 300 nm Smart Drug Release Folic acid [29] 4.5 µm (max) -Food industry Whey protein [30] 56. The feasibility and kinetics crosslinking reaction between the healing agent and curing agent were studied by mixing AESO and TMPMP.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In-situ polymerization Dual capsules: (1) Diglycidyl tetrahydro-ophthalate (2) PETMP [24] 50 µm a 100 µm a -Self-healing composite Dual capsules: (1)Epoxy prepolymer (EC 157) (2) PETMP [25] 10-35 µm 5-45 µm -Self-healing composite Solvent Evaporation PETMP [26] 160 µm a -Self-healing composite epoxy resin (diglycidyl ether of bisphenol A) [32] 575 µm a -Self-healing composite Dual capsules: (33) (1) epoxy resin (DGEBPA) (2) PETMP [33] 364 µm a 334 µm a 3-6 µm Self-healing composite Budesonide and Epigallocatechin gallate (EGCG) [27] 165 nm to 1.2 µm -Coating of drug Paclitaxel [28] 600 nm-6 µm 300 nm Smart Drug Release Folic acid [29] 4.5 µm (max) -Food industry Whey protein [30] 56. The feasibility and kinetics crosslinking reaction between the healing agent and curing agent were studied by mixing AESO and TMPMP.…”
Section: Methodsmentioning
confidence: 99%
“…Ahangaran et al used PMMA as shell material for encapsulation of a mercaptan and an epoxy with low viscosity (0.50-0.60 Pa • s) by solvent evaporation method [25]. Truong et al reported microencapsulation of a reactive mercaptan compound using solvent evaporation method, they employed UV rays to initiate thiol-ene reaction to form the microcapsule's shell [26].…”
Section: Introductionmentioning
confidence: 99%